Istiqomah dalam Al-Qur`an (Perspektif Abu Bakar Jabir Al-Jazairi) - Zikra Wahyuni Putri; Dapit Amril (IAIN Batusangkar, 2022)
The main problem in this journal is how to interpret istiqomah in the Qur'an according to the perspective of Abu Bakar Jabir al-Jazairi. The purpose of this study is to find out the interpretation of istiqomah verses in the Qur'an based on the perspective of Abu Bakar Jabir al-Jazairi in his interpretation of Aisar at-tafasir li Kalamil 'Aliyyil Kabir. The type of research used is library research. While the data collection technique that the author uses is to collect all data regarding istiqomah in the Qur'an and then the author analyzes the verses of the Qur'an through the term istaqoma. The interpretation method used is the maudu'i method. In the management of interpretive data by Abu Bakar Jabir al-Jazairi, a character study approach, content analysis and a bil ma'tsur interpretation approach are used. This study also discusses the meaning of istiqomah according to Abu Bakar Jabir al-Jazairi and the reward for istiqomah according to Abu Bakar Jabir al-Jazairi.